Ciclos de vida de los regímenes de competencia: análisis de la evolución de nuevos sistemas - López-Galdós, Marianela (2022)
The article analyzes in an original way the patterns of evolution of competition systems at a global level. It establishes patterns of evolution and aims to identify those factors that influence the success or failure of the progression of competition systems.